2017
DOI: 10.15282/jmes.11.2.2017.4.0238
|View full text |Cite
|
Sign up to set email alerts
|

Seakeeping performance of a rounded hull catamaran in waves using CFD approach

Abstract: Prediction of the seakeeping performance of a ship in the earlier ship's design step is necessary to ensure the safety of navigation during sailing. To accommodate such a demand, this research proposes to analyse the seakeeping performance of a rounded hull catamaran. The vertical motion of the catamaran including the heave and pitch motions were quantified by her Response of Amplitude Operator (RAO). The Computational Fluid Dynamic software was used to develop the model, where several effects of various Froud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Although, the pitch motion decreases from 3.851286 ⁰ to 0.622232 ⁰. The result also showed that the higher the Froude number, the more the slope of the post-peak descending region will be and the lower of Froude number was prone to down degrade the seakeeping performance of the 'deep-V' catamaran due to the higher response of heave and pitch motion (Fitriadhy, Razali, & AqilahMansor, 2017) and (Vakilabadi et al, 2014).…”
Section: Effect Of Froude Number (Fr)mentioning
confidence: 96%
“…Although, the pitch motion decreases from 3.851286 ⁰ to 0.622232 ⁰. The result also showed that the higher the Froude number, the more the slope of the post-peak descending region will be and the lower of Froude number was prone to down degrade the seakeeping performance of the 'deep-V' catamaran due to the higher response of heave and pitch motion (Fitriadhy, Razali, & AqilahMansor, 2017) and (Vakilabadi et al, 2014).…”
Section: Effect Of Froude Number (Fr)mentioning
confidence: 96%
“…Referring to the transport model discussed above, the viscosity has been taken into account that presents the high gradients near solid wall layers. Therefore, it is very important to have a sufficient amount the number of grid points in the boundary layers to properly capture the high gradient [21]. Here, an appropriate estimation of cell meshing size, for Navier-Strokes simulation, depends on the wall variable + to measure the viscosity effect region as written in Eq.…”
Section: Turbulent Modelmentioning
confidence: 99%
“…This paper presents a CFD simulation approach for the extension work from [21,22] to access the performance of propeller by KT, KQ, and Ƞ of the propeller. Here, a commercial CFD software, namely NUMECA Fine TM /Turbo v12.2 is utilized by grid generation, flow solver and post-processing capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…The Froude number of 0.4 was also introduced as the situation in which lowering the lateral spacing notably enlarges the drag force [33]. Similarly in the case of encountering sea waves, the reduction in hull lateral separation intensifies dynamic trim and sinkage [34]. Or even when there is a relative motion between two neighboring bodies, the slower one experiences stronger hydrodynamic loads as well as greater trim and sinkage due to the interaction [35].…”
Section: Introductionmentioning
confidence: 99%